Molecular Evaluation of Efficacy of Freshwater and Marine Acellular Fish Skin Matrixes in Reconstruction of Ventro- Lateral Hernia in Bucks - Bassam H. Gumaa; Ahmed H. F. AL-Bayati (Indian Journal of Forensic Medicine & Toxicology, 2021)
The objective of present study is to compare between the effectiveness of freshwater and marine acellularfish skin (AFS) matrices on the reconstruction of large abdominal wall hernias in Iraqi bucks using ofmolecular evaluation depending on Real Time-quantification Polymerase Chain Reaction (RT-qPCR)technique to investigate the levels of basic-fibroblast growth factor (b-FGF) and vascular endothelial growthfactor (VEGF) genes during the healing process of the abdominal wall hernias. Ventral-lateral abdominalwall hernias (7X7cm) were induced experimentally in 18 bucks. Thirty days post-inducing of hernias, theanimals were divided randomly into two main groups (9 Bucks/ group). The hernias in animals of group (A)were treated with onlay implantation of freshwater AFS sheet. While, the hernias in animals of group (B)were treated with onlay implantation of marine AFS sheet. Molecular evaluation was depended at 2, 8, and12 weeks post-treatment of hernias. The results revealed that the significant elevation of the level of b-FGFbetween treatment groups was at week 8th in group B and at week 12th in group A. While, the significantelevation of level of VEGF between treatment groups was recorded in group A, 12 week post-treatment.